Non-linear electron dynamics in dilute nitride alloys - Spasov, Spas (2009)
This thesis describes an experimental study of the electronic properties of the dilute nitride GaAs1¡xNx alloy. This is a semiconductor belonging to a class of highly mismatched III-N-V alloys. The incorporation of isoelectronic N on the pnictide (e.g. As) site of GaAs gives rise to a highly localised electronic state, whose energy level is resonant with the continuum of conduction band (CB) states of the host GaAs lattice. The interaction between these two sets of states causes the formation of a fully developed energy gap in the CB of the host crystal and makes possible the observation of a novel type of negative differential conductance (NDC) effect. The NDC in GaAs1¡xNx is qualitatively different from the NDC occurring in transferred electron devices (Gunn diodes) and semiconductor superlattices (SLs) and has potential for novel terahertz (THz) device applications. The emphasis of the thesis is on the experimental study of the non-linear electron dc dynamics in GaAs1¡xNx that arises when electrons are accelerated in the non-parabolic CB of GaAs1¡xNx. It also includes an investigation of the coupling of electrons to THz radiation by the measurement of harmonic generation of ac current and of changes in the dc conductivity in the presence of an applied THz radiation. The rectification effects revealed in our experiments indicate that the mechanism giving rise to NDC is a fast ( 10¡12 s) process. The fast response in time of the current is in agreement with previous calculations of the ac electron dynamics in GaAs1¡xNx predicting that the maximum response frequency associated with the NDC is governed by the time of ballistic acceleration of electrons to the N-level and that this lies in the THz frequency range. The experimental results are discussed in terms of different theoretical models and mechanisms, including the band anticrossing model, space-charge-limited current instabilities, magnetophonon resonance and classical rectification theory.